Molecular Quadrupole Moments Promote Ground‐State Charge Generation in Doped Organic Semiconductors. (9th September 2020) - Privitera, Alberto; Londi, Giacomo; Riede, Moritz; D'Avino, Gabriele; Beljonne, David
Abstract: The role of local environmental interactions on the generation of free charge carriers in doped organic layers is investigated. Via a classical micro‐electrostatic model, a dual effect of molecular quadrupole moments of host and dopant molecules on doping is demonstrated. Namely, electrostatic interactions ease ionization of the dopant by altering the energy level alignment between the host and the dopant and reduce the barrier for charge dissociation by flattening the energy landscape around the ionized dopants. These results indicate that tailoring molecular quadrupole moments of the host and/or dopant are an attractive strategy toward improved doping efficiency in organic semiconductors. Abstract : Micro‐electrostatic calculations demonstrate that molecular quadrupole moments of host and dopant molecules fundamentally affect the molecular doping of organic semiconductors. Namely, both the dopant ionization and the charge dissociation steps are facilitated by the rearrangement of the frontier energy levels of the host/dopant molecules due to the microscopic electrostatic interactions.